Preoperative intralesional injection of triamcinolone acetonide for a large head and neck lymphangioma in a baby: a case report - Julius July; Sophie Peeters (Paediatrica Indonesiana, 2017)
Lymphangiomas (LMs) are uncommon congenital malformations of the lymphatic system, with an estimated incidence of one in 2,000 to 4,000 live births.1 About half of these lesions are diagnosed at birth, and by two years of age, 90% of those with lesions have been diagnosed.2 Histologically, LMs are benign lesions; however, they can pose a serious threat to the patient due to possible growth into surrounding structures, sometimes causing life-threatening complications. Treatment of large head and neck lymphangiomas in young infants is very challenging, due to the risk of surgical complications. Further challenges include the limited volume of blood loss that infants can tolerate, the lack of the option for radiotherapy or radiosurgery, and the high chance of life-threatening complications if the LM is not treated. Here, we report a case of a two-month-old baby girl presenting with a large head and neck lymphangioma. She was successfully treated with intralesional triamcinolone acetonide injections, followed by surgical resection of the lesion.